Prevalence, characteristics and additional stroke risk stratification: an analysis of the Atrial Fibrillation cohort within the REMEDY study - Cupido, Blanche J (Department of Medicine, 2017)
Background: Atrial fibrillation (AF) is the most common arrhythmia and may be complicated by embolic stroke. It is also associated with a significant risk of heart failure and mortality. The burden of rheumatic heart disease remains great in the developing world. The prevalence of AF in those with rheumatic heart disease is in the order of 20% with a resultant 17-fold increased risk of embolic stroke. Over time, many other risk factors for stroke in the AF population have been described. Stroke risk stratification tools such as the CHADS₂ (Congestive heart failure, hypertension, age of 75 or older, diabetes mellitus or stroke/TIA) and CHA₂DS₂VASc (with the addition of a second age category, female gender, and peripheral artery disease) scores have been developed. These are used to assess the need for anticoagulation and have been well validated. These scores have traditionally excluded those patients with valvular AF. Valvular AF has not been studied extensively in the contemporary era. Oral anticoagulation had previously been advised in all patients with valvular AF. Little is known however about outcomes for stroke and mortality in this cohort of patients. Furthermore, the utilization of the CHADS₂ and CHA₂DS₂VASc scores may provide incremental benefit in prognostication and resultantly, both more diligent prescription of anticoagulation and improved outcomes. Objectives: The objectives of this study were as follows - 1. To determine the prevalence of AF in the Global Rheumatic Heart Disease Registry (the REMEDY study) and in the Groote Schuur Hospital (GSH) cohort. 2. To assess the demographic, social and clinical characteristics of patients with AF in the REMEDY study and in the GSH cohort. 3. To assess the frequency of CHADS₂ and CHA₂DS₂VASc risk factors in the GSH cohort and to calculate a CHADS₂ and CHA₂DS₂VASc score on each of the patients with AF. 4. To establish whether CHADS₂ and CHA₂DS₂VASc scores further increase the risk of stroke and death in this cohort of patients with valvular AF. Methods: This is a substudy of the Global Rheumatic Heart Disease Registry (the REMEDY study). We assessed those with AF from the entire cohort for prevalence and outcome data. Patients with ECG or Holter proven AF from the GSH cohort were further risk stratified using the CHADS₂ and CHA₂DS₂Vasc scores. Clinical data was obtained from folder reviews and telephonic interviews. The CHADS₂ and CHA₂DS₂Vasc scores for each patient in the GSH cohort were calculated. Patients were followed up for 2 years and information pertaining to death and stroke were obtained from folder reviews. These were then correlated with the CHADS₂ and CHA₂DS₂Vasc scores. Results: A total of 2624 REMEDY patients were analysed. Of these, 22% in the total cohort (586 of 2684 patients) and 38.2% in the GSH cohort (187 of 489 patients) had AF. These patients were older (35 years vs. 25 years, p<0.0001), more likely to be female (73.1% vs. 65.6%, p=0.001) and more frequently had a history of congestive heart disease (41.0% vs. 33.3%, p=0.001) when compared to those in sinus rhythm. They also had significantly more strokes (13.8% vs. 5%, p<0.0001) and a poorer NYHA class (NYHA III& IV 30.8% vs. 25.2%, p=0.002). The cohort with AF had more severely impaired left ventricular (LV) function compared to those in sinus rhythm (Ejection fraction (EF) 57% vs. 61%. P<0.0001). The presence of a larger left atrial (LA) size, spontaneous echo contrast and LA thrombus was much greater in the AF cohort. Of those patients in AF, only 68% had received a prescription for warfarin. The GSH cohort was risk stratified using the CHADS₂ and CHA₂DS₂VASc scores. Twenty-three percent of patients had a CHADS₂ score of 0 and 27.7% of 1. When the same cohort was scored using the CHA₂DS₂VASc score, only 5.4% had a score of 0; this difference was mainly driven by the additional category of female gender. The patients in our cohort were young (median age 28 years) and had few comorbidities. Despite this, patients with AF did significantly worse than those in sinus rhythm, with a stroke rate of 4.6% and a mortality rate of 13.1% observed at 2 years (compared to a 1.5% stroke rate and 5.5% mortality rate for those in sinus rhythm). The presence of any additional comorbidities significantly reduced survival in both the short and long term. Greater CHA₂DS₂VASc score categories (CHA₂DS₂VASc 1 and CHA₂DS₂VASc 2 or more) conferred an incrementally higher risk of death. Conclusion: In a contemporary cohort of patients with rheumatic heart disease, AF is common with a prevalence of 22-39%. These patients were older and exhibited features of more advanced disease both clinically and on echo, compared to their sinus rhythm counterparts. The mortality and stroke rates in the AF group were high despite the relatively young age of this cohort. Mortality and stroke increased significantly and incrementally with each greater CHA₂DS₂VASc score category. Given the differences in chronicity between RHD in the developed world (i.e., disease of older people) and RHD in developing countries (i.e., disease of the young), these results cannot be extrapolated to those living in the first world.